Eco-neurobiology, and how the environment shapes our brains - Grabrucker, Andreas M. (Cambridge Scholars Publishing, 2019)
Eco-neurobiology is a field of neuroscience that investigates how environmental factors impact the brain through development and aging. This book takes the reader on a journey through the most recent findings in this field, covering how non-genetic factors influence our brain and may contribute to the development of disorders, as well as the everyday function of our minds. The things we eat, the stressfulness of our lives, and traumatic events all have effects on our brains that we are just beginning to understand.